Alterations in the metabolic and cardiorespiratory response to exercise in Huntington's Disease. (September 2018) - Steventon, J.J.; Collett, J.; Furby, H.; Hamana, K.; Foster, C.; O'Callaghan, P.; Dennis, A.; Armstrong, R.; Németh, A.H.; Rosser, A.E.; Murphy, K.; Quinn, L.; et al.
Abstract: Background: Limited data suggests that an altered metabolic and cardiorespiratory exercise response may affect exercise performance in individuals with Huntington's disease (HD). There is no clear exploration of the response in individuals at different stages of the disease or in relation to genetic markers. This study aimed to examine the exercise response and recovery of HD participants, and the relationship to genetic and clinical markers. Method: HD gene-positive participants (n = 31; 9 pre-manifest; 22 manifest HD) and a healthy control group (n = 29) performed an incremental exercise test until exhaustion. Performance, cardiorespiratory, metabolic and perceptual responses to exercise were determined from a maximal cycle ergometer test throughout the exercise test and during a recovery period. Results: During sub-maximal exercise, metabolic (lactate levels, oxygen uptake) and cardiorespiratory markers (heart rate) were elevated in HD participants compared to controls. Lactate elevation was specific to pre-manifest HD participants. Work capacity was reduced in both pre-manifest and manifest HD participants with tests terminated with no difference in metabolic, perceptual or cardiorespiratory markers. Submaximal oxygen uptake was correlated with motor score, whilst peak measures were unrelated to genetic or clinical markers. Heart rate recovery was attenuated in pre-manifest and manifest HD participants. Conclusions: Our findings confirm metabolic and cardiorespiratory deficits reduce exercise performance and affect recovery from an early stage in HD, with submaximal deficits related to phenotypic expression. Exercise capacity appears to be limited by an altered movement economy, thus clinicians should consider an altered exercise response and recovery may affect prescription in HD. Highlights: People with HD have an altered metabolic and cardiorespiratory response to exercise. Physiological recovery from exercise is affected in people with HD. The altered response has implications for exercise prescription outcomes in HD.